Financial Resistance of Islamic Banks in Middle East Region: A Comparative Study with Conventional Banks During the Arab Crises - Hani El-chaarani; Nashwa Shaker Ragab (International Journal of Economics and Financial Issues, 2018)
The research aims to empirically test the impacts of political crisis and economic recession during 2010-2015 on the performance and financial behavior of Islamic and conventional banks in the Middle East region. The period of the study (2010-2015) is divided to three phases (stability, economic crisis and political crisis) to reveal the implication of political and economic crises on the performance and financial behavior of Islamic and conventional banks, first, by tracking the sample of Islamic banks during different phases, then, by comparing the sample of Islamic banks with a paired and non-paired samples of conventional banks. The results of this study reveal negative impacts from politic crises and economic recession on the performance of Islamic banks. The results also reveal that the Islamic banks increase their capital adequacy and focus on the reduction of costs to increase the efficiency level during politic crises while they focus on increasing liquidity and assets quality during economic crisis. Additional analyses show the absence of any significant difference between the performance of Islamic and conventional banks during the periods of stability and crises. Finally, this research reveals that the conventional banks have more ability to manage their assets quality and their expenses, whereas the Islamic banks have more capacity to manage their liquidity level. This research reveals the new challenges facing Islamic and conventional banks in Middle East countries. The last Arab spring and oil prices drops highlight a new issue that has not received the needed attention and provide a natural experiment to evaluate the financial resistance and capacity of both Islamic and conventional banks in the Middle East region.  Keywords: Islamic banks, conventional banks, financial performance, financial behavior, capital structure. JEL Classifications: G20, G32